Quaternary alkaloids of berberis barandana vidal - Castillo, Amorita Villegas 1922-
From the root-trunk of berberis baranda Vidal (Philippine Berberidaceae), two more quarternary alkaloids aside from berberine were isolated. Using the sodium borohydride reduction method, the quarternary alkaloidal portion was worked up to yield a phenolic base (0.02% yield), m.p. 204-205(degrees), and a nonphenolic base (0.013% yield), m.p. 144-145(degrees). Mixed melting point determination, paper chromatography, molecular weight determination, elementary analysis and methoxyl determination proved these bases to be tetrahydrojatrorrhizine and tetrahydropalmatine, respectively. The identity of the phenolic base was confirmed by methylation to its methyl ether, tetrahydropalmatine. The stem portion was similarly worked up to yield the same quarternary bases as in the root-trunk.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines, 1961.
Keywords: Alkaloids